TOURISM DEVELOPMENT DISTORTS THE BALINESE CULTURE? - Wirawan, Matt Oka; Wiwiek Agustina, Ni Ketut (Pusat Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Nusa Dua Bali, 2004)
Attitudes to tourism development vary greatly among different approaches.To cautionary approach, this inter nation phenomenon is seen as fruiting ahulk of various physical and social excess. To others, adaptation and scientificapproaches, when well planned, organized, implemented, and conirollcd.tourism development can bear lots of advantages both to the tourists andhost countries. In Bali, many researchers from different scientificbackgrounds found enough empirical evidence that tourism developmentgenerates numbers of beneficial influence for the deselopment of theBalinese culture.